Material Semikonduktor ZnO Didoping Cu Untuk Meningkatkan Konduktivitas Thermal - Bayu Prabandono; Agus Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
LGV (liquefied gas for vehicle) is one of the alternative fuel, which prioritized for a fuel diversification program of transportation sector in Indonesia. Having different characteristics and properties of gasoline fuel, the use of LGV fuel will have an effect on the working parameters of an engine. Based on that, this research is conducted to analyze the effect of using LGV fuel at a mass air flow rate and fuel rate in passenger cars. Through this research also expected as an act to support the diversification fuel program that proclaimed by Indonesia Government. Passenger cars used in this research have a different engine capacity, i.e., 1200 cc and 1500 cc. Measurement of mass air flow rate and fuel rate are performed with the throttle position variation (absolute throttle position) from 14% to 30% on third gear. The results obtained indicate that there is a decrease in air and fuel flow rate of 4% for the test car Honda Mobilio (1500 cc) and 2% for Mitsubishi Mirage (1200 cc). In addition, the air fuel ratio (AFR) of LGV fuel has the same range like fuel petrol mixing, the value of the measured air fuel ratio is 14.4-14.8 for Honda Mobilio and 13.5-14.6 for Mitsubishi Mirage. The lower value of fuel flow rate than gasoline fuel, prove that the use of the LGV fuel is more efficient and cheaper (due to the LGV price) than gasoline. In addition, LGV fuel also more environmentally friendly than gasoline fuel as seen from result of emission testing done by the most researchers.